2013
DOI: 10.1007/s00394-013-0607-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of dietary type with fecal microbiota in vegetarians and omnivores in Slovenia

Abstract: Long-term vegetarian diet contributed to quantity and associated bacterial community shifts in fecal microbiota composition. Consumption of foods of animal origin (eggs, red meat, white meat, milk, yoghurt, other dairy products, fish and seafood) and vegetarian type of diet explained the largest share of variance in microbial community structure. Fecal microbiota composition was also associated with participants' age, gender and body mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(130 citation statements)
references
References 51 publications
10
115
0
5
Order By: Relevance
“…Interestingly, the respective diets brought about a transcriptional response among the gut microbiota that was consistent with previously reported differences in gene abundances between herbivorous and carnivorous animals [61]. In other studies, members of the Clostridium clusters IV and XIVa have been found to be enriched in the faeces of omnivores compared to vegetarians and lactovegetarians, who generally consume higher proportions of carbohydrates as part of their diet [97][98][99]. These clusters of bacteria are noted for their ability to convert dietary fibre to SCFAs.…”
Section: Modulation By Dietsupporting
confidence: 87%
See 1 more Smart Citation
“…Interestingly, the respective diets brought about a transcriptional response among the gut microbiota that was consistent with previously reported differences in gene abundances between herbivorous and carnivorous animals [61]. In other studies, members of the Clostridium clusters IV and XIVa have been found to be enriched in the faeces of omnivores compared to vegetarians and lactovegetarians, who generally consume higher proportions of carbohydrates as part of their diet [97][98][99]. These clusters of bacteria are noted for their ability to convert dietary fibre to SCFAs.…”
Section: Modulation By Dietsupporting
confidence: 87%
“…Associated with Prevotella-rich enterotype [62] Faster gut transit time compared to high protein and animal fat diet [62] Omnivorous compared to vegetarian and lactovegetarian [97][98][99] Increased Clostridium clusters IV and XIVa [97][98][99] Not reported High-fat, simple carbohydrate ''Western'' diet [38,40] Increased Firmicutes, decreased Bacteroidetes [38,40] Diet-induced obesity. Subsequent transplantation of obese microbiota to germ free mice increased adiposity [40] Reduced carbohydrate intake [63] Reduced Bifidobacterium, Roseburia spp.…”
Section: Dietmentioning
confidence: 99%
“…This was due to a higher abundance of Bacteroides (e.g. Prevotella, Bacteroides thetaiotaomicron, Bacteroides fragilis) and a decreased abundance of Clostridium cluster XIVa and IV [41][42][43]. In humans [44] and mice [45], Western diet was associated with reduced microbial diversity, increased relative abundance of Firmicutes and an underrepresentation of the genus Prevotella.…”
mentioning
confidence: 98%
“…Germans on vegetarian or vegan diet showed a modest decrease in Bacteroides , Bifidobacterium and Escherichia coli compared with matched omnivores (Zimmer et al ., 2012). Vegetarians from Slovenia demonstrated a higher faecal concentration of the Bacteroides‐Prevotella group than omnivores (Matijašić et al ., 2014). A small group of US vegetarians showed a non‐significant increase in Prevotella enterotype (Wu et al ., 2011).…”
Section: Biome Engineering: Modifying the Nutrient Inputmentioning
confidence: 99%